Pengaruh Pelatihan Warehouse Management System Terhadap Kelancaran Produksi pada PT. Mcdermott Batam - Firda Fadila; Iik Suryati; Yusi Rahmawati (Universitas 17 Agustus 1945, 2025)
This research is motivated by the limited knowledge of human resources in operating Warehouse Management System (WMS). The purpose of this study is to analyze the influence of WMS training materials, methods, and trainers on production smoothness at PT. McDermott Batam and to analyze the influence of training duration on production smoothness. This study uses a quantitative method with a simple linear regression analysis approach. The population of the study were employees of PT. McDermott Batam, with a sample of 67 respondents selected using the Simple Random Sampling (SRS) technique and calculated using the Slovin formula with a margin of error of 10%. Data were collected through observation, interviews, documentation, questionnaires, and literature studies, then analyzed using SPSS software version 30. The results showed that WMS training had a positive and significant effect on production smoothness with a significance value of 0.001 <0.05 and tcount 8.565> ttable 1.997. In addition, WMS training contributed 53% to production smoothness. Thus, increasing the effectiveness of WMS training can be an important strategy in improving production smoothness at PT. McDermott Batam.